2022
DOI: 10.1038/s41467-022-34158-z
|View full text |Cite
|
Sign up to set email alerts
|

Generating intense electric fields in 2D materials by dual ionic gating

Abstract: The application of an electric field through two-dimensional materials (2DMs) modifies their properties. For example, a bandgap opens in semimetallic bilayer graphene while the bandgap shrinks in few-layer 2D semiconductors. The maximum electric field strength achievable in conventional devices is limited to ≤0.3 V/nm by the dielectric breakdown of gate dielectrics. Here, we overcome this limit by suspending a 2DM between two volumes of ionic liquid (IL) with independently controlled potentials. The potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 58 publications
0
28
0
Order By: Relevance
“…Most recently, ref. 36 and 37 reported realizations of an electric field up to 3.5 V nm −1 across a WSe 2 bilayer using ionic liquid gates, one order of magnitude higher than required in this work. In Fig.…”
Section: Resultsmentioning
confidence: 80%
“…Most recently, ref. 36 and 37 reported realizations of an electric field up to 3.5 V nm −1 across a WSe 2 bilayer using ionic liquid gates, one order of magnitude higher than required in this work. In Fig.…”
Section: Resultsmentioning
confidence: 80%
“…The sensor's response is noted as a variation in drain current when an electric field is applied usually, investigated using field-effect transistors (FETs). 67 In this section, we analyzed the modulated sensitivity of PNG toward SO 2 detection by examining the impact of the external electric field. The electric field along the z-direction (perpendicular to the surface) and intensity of −0.4 to +0.4 V/ Å are taken into consideration.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Many prior studies suggested that using an external electric field to modify the performance of 2D materials as a gas sensor is an effective method. , Electric fields cause changes in the carrier density ( E -field causes polarization of charge density) produced in a material by the field at its surface, which further alters the response of the sensor toward the adsorbate. The sensor’s response is noted as a variation in drain current when an electric field is applied usually, investigated using field-effect transistors (FETs) …”
Section: Resultsmentioning
confidence: 99%
“…[2][3][4] In transistors, the large capacitance leads to unrivaled performance in low-voltage operation [10][11][12] and sub-threshold swing. 5,12,13 It also enables the observation of physical phenomena, such as gate-induced superconductivity (at carrier densities ∼ 10 14 cm 2 ), 4,[14][15][16][17][18][19][20][21][22][23][24][25][26] the quenching of the band gap of two-dimensional (2D) semiconductors, 27,28 or the possibility to perform precise spectroscopic measurements of semiconducting band gaps (ionic-gate spectroscopy). 5,9,[29][30][31][32][33][34][35][36][37] These results have been enabled by liquid electrolytes, either ionic liquids and ionic solutions (ions dissolved in liquid electrolytes), or ion gels, i.e., ionic liquids or ions dispersed in a polymer matrix (such as polyethylene oxide), ideal for gating applications 4 because of their high electrochemical stability [2][3][4] and relatively large ionic conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…39,40 Electrolyte back-gated devices would drastically expand the range of carrier density, and allow phenomena such as gate-induced superconductivity to be studied by ARPES (or, similarly, by scanning tunneling spectroscopy). Ionic double gated devices -which enable the applications of electric fields in excess of 3 V/nm perpendicular to 2D semiconductors to quench their gap-provide another pertinent and timely example, 27,28 since they require combining an top and back ionic-gate electrodes. These and other types of experiments cannot be performed using exclusively top ionic-gate electrodes, and to make them possible it is necessary to find solid-state electrolytes (SSE) [41][42][43][44] that can be employed reliably in a back-gate configuration, with performance comparable to that of top ionic gates.…”
Section: Introductionmentioning
confidence: 99%